2020
DOI: 10.1155/2020/1285068
|View full text |Cite
|
Sign up to set email alerts
|

LRG1 May Accelerate the Progression of ccRCC via the TGF-β Pathway

Abstract: Clear cell renal cell carcinoma (ccRCC) accounts for 60-70% of renal cell carcinoma (RCC) cases. It is an urgent mission to find more therapeutic targets for advanced ccRCC. Leucine-rich a-2-glycoprotein 1 (LRG1) is a secreted protein associated with a variety of malignancies. Our study focused on the expression and mechanism of LRG1 in ccRCC based on data from The Cancer Genome Atlas (TCGA) and provided primary verification including LRG1 expression detection, LRG1 gene methylation detection, and downstream s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Moreover, LRG1 has been often over-expressed in multiple diseases. 35 , 36 Similarly, our findings demonstrated that LRG1 was highly-expressed in NP cells and tissues upon IDD. Meanwhile, a previous study revealed that LRG1 knockdown enhances osteoblast viability and collagen synthesis, and suppresses osteoblast apoptosis via promotion of the TGF-β1/SMAD signaling pathway in osteoporosis.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, LRG1 has been often over-expressed in multiple diseases. 35 , 36 Similarly, our findings demonstrated that LRG1 was highly-expressed in NP cells and tissues upon IDD. Meanwhile, a previous study revealed that LRG1 knockdown enhances osteoblast viability and collagen synthesis, and suppresses osteoblast apoptosis via promotion of the TGF-β1/SMAD signaling pathway in osteoporosis.…”
Section: Discussionsupporting
confidence: 78%
“…Increases with clinical stage [ 12 , 177 , 259 ] Tumour tissue Associated with higher recurrence rate and worse recurrence-free survival [ 256 ] Prostate Serum Elevated in fatal prostate cancer. Positively correlated with high risk of disease progression and mortality [ 260 ] Renal Tumour tissue Overexpressed in clear renal cell carcinoma and negatively related to patient survival [ 261 ] Retinal Tumour tissue Highly expressed in retinoblastoma [ 262 ] List of publications where LRG1 is discussed as a potential biomarker for the diagnosis, prognosis and monitoring of various cancer types. The samples used for LRG1 detection (serum, plasma, tissue section or urine), together with the main findings reported in the studies, are included.…”
Section: Reviewmentioning
confidence: 99%
“…On the other hand, it has been documented that LRG1 can affect leiomyomas through TGF-β signaling. 40,41 Therefore, it is suggested that conducting a series of screenings to assess vitamin D concentration and subsequently maintaining its levels within the appropriate range through the use of vitamin D supplements could significantly contribute to the prevention or treatment of leiomyomas.…”
Section: Discussionmentioning
confidence: 99%